Starlink satellite project impact on the internet provider service in emerging economies - Yarnaphat Shaengchart; Tanpat Kraiwanit (Research in Globalization, 2023)
Starlink primarily focuses on delivering high-speed, low-latency broadband Internet in remote and rural locations globally. This study aims to investigate the Starlink satellite project's impact on the Internet provider service in emerging economies. A quantitative approach was used, and an online questionnaire was conducted to collect data from a convenience sample of 617 participants in Thailand. Demographic variables (i.e., gender, age, education, status, and income), user behaviour variables (i.e., computer, laptop, smartphone, tablet, wearable device, time, Internet duration, home Internet, and mobile Internet), and social media variables (i.e., Facebook, Instagram, Twitter, TikTok, and Youtube) were the independent variables. Binary regression analysis was performed to analyse the data. The findings revealed that the Starlink satellite project's impact on the Internet provider service in this emerging economy could be described by gender, education, tablet, wearable device, Internet time, Internet duration, Facebook, and Twitter. It is recommended to inform people of the effects of the Starlink satellite project on Internet service providers in developing economies. Satellite Internet access has transformed the expansion of professional development opportunities for those who live in remote, rural, and underserved areas. Due to the lack of terrestrial Internet infrastructure, users of satellite Internet can now access specialised resources that were previously inaccessible. Satellite Internet has also made it possible for people living in remote areas to benefit from opportunities for career advancement and more.
Keywords: 330; Emerging economy; Internet Provider; Service; Starlink SATELLITE project